Computerized tomography-guided sphenopalatine ganglion pulsed radiofrequency treatment in 16 patients with refractory cluster headaches: Twelve- to 30-month follow-up evaluations. (February 2016) - Fang, Luo; Jingjing, Lu; Ying, Shen; Lan, Meng; Tao, Wang; Nan, Ji
Background: Sphenopalatine ganglion percutaneous radiofrequency thermocoagulation treatment can improve the symptoms of cluster headaches to some extent. However, as an ablation treatment, radiofrequency thermocoagulation treatment also has side effects. Objective: To preliminarily evaluate the efficacy and safety of a non-ablative computerized tomography-guided pulsed radiofrequency treatment of sphenopalatine ganglion in patients with refractory cluster headaches. Methods: We included and analysed 16 consecutive cluster headache patients who failed to respond to conservative therapy from the Pain Management Center at the Beijing Tiantan Hospital between April 2012 and September 2013 treated with pulsed radiofrequency treatment of sphenopalatine ganglion. Results: Eleven of 13 episodic cluster headaches patients and one of three chronic cluster headaches patient were completely relieved of the headache within an average of 6.3 ± 6.0 days following the treatment. Two episodic cluster headache patients and two chronic cluster headache patients showed no pain relief following the treatment. The mean follow-up time was 17.0 ± 5.5 months. All patients enrolled in this study showed no treatment-related side effects or complications. Conclusion: Our data show that patients with refractory episodic cluster headaches were quickly, effectively and safely relieved from the cluster period after computerized tomography-guided pulsed radiofrequency treatment of sphenopalatine ganglion, suggesting that it may be a therapeutic option if conservative treatments fail.